Response of rubber based engine mounts with SBR as the core rubber. (December 2018) - Idrees, Mohammed; Rajendra Prasad, V.B.S.
Abstract: Nowadays the most important and basic requirements of automotive industry are vehicle stability, driving ability, and passenger comfort; and all of these need the control of vibrations to some extent. Engine is main source of power to a vehicle but it produces vibrations, thereby reducing the performance of a vehicle. These vibrations can be eliminated by the use of engine mounts, using which an engine is mounted on the chassis of the vehicle. Its basic function is to rightly hold the engine and transmission system on chassis of the vehicle. A good engine mount should firstly isolate the engine vibrations caused by engine disturbances and next they should isolate the transfer of vibrations from engine to chassis and reversely. In view of this an attempt is made to study the performance of two elastomeric engine mounts of two separate origin with SBR (Styrene Butadiene Rubber) as their core rubber, laying main focus on their vibration isolation characteristics. The selected engine mounts are elastomeric mounts for a heavy commercial vehicle with rubber as core to resemble a sandwiched structure. In the present work firstly the damping properties and vibration isolation characteristics of SBR are identified by using a sandwiched structure. Then the engine mount are modelled using this SBR as a Hyper-elastic rubber using the best fit Hyper-elastic material model. SBR is selected due to its wide range of applications in automobile industry. The performance of two engine mounts is studied for static, harmonic and time varying loads.